Swallowing outcomes for patients with oropharyngeal squamous cell carcinoma treated with primary (chemo)radiation therapy receiving either prophylactic gastrostomy or reactive nasogastric tube: A prospective cohort study. (10th March 2017) - Goff, D.; Coward, S.; Fitzgerald, A.; Paleri, V.; Moor, J.W.; Patterson, J.M.
Abstract : Objectives: There is currently no consensus on the optimal feeding route for an oropharyngeal squamous cell cancer (OPSCC) patient without pre‐existing dysphagia undergoing chemoradiotherapy. This study aimed to compare the swallowing outcomes for OPSCC patients fed via either prophylactic RIG (pRIG) or reactive nasogastric tube (rNGT). Design: A prospective cohort study. Setting: Four head and neck cancer centres in the North of England Cancer Network. Participants: Fifty‐three participants with OPSCC, on a normal diet pre‐(chemo) radiotherapy. Main outcome measure: Swallowing outcomes for patients with rNGT and pRIG were compared using the following outcome measures administered prospectively at pre‐treatment, three and 12 months post‐treatment: MD Anderson Dysphagia Inventory (MDADI), Performance Status Scales (Normalcy of Diet), timed water swallow test. Results: Twenty‐three patients received pRIG while 30 were planned for a rNGT. No differences in demographics were found between the groups. The rNGT group had a clinically significant higher score on MDADI at 12 months post‐treatment. No significant difference was found on a timed water swallow test or diet texture scale. Conclusions: There is no statistical difference for swallowing outcomes in either group. However, patients' in the rNGT group reported a clinically meaningful difference at 1 year, with a trend for them to do better across all measures. Neither group returned to their baseline swallowing function. Further research with a larger sample size is indicated.